Identification of Characteristic Flavor Compounds in Tibetan Sheep, Goat and Local Sheep Meat Using GC-IMS Combined with HS-SPME-GC-MS and Chemometrics - Wang, Mengran; Li, Mengqi; Zhu, He; Li, Yujie; Ma, Jinlin (International Journal of Materials Science and Technology Studies, 2026)
This study focuses on Tibetan lamb meat from the Qinghai Tibet Plateau, local sheep meat from Shandong, and goat meat. Using a combination of headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME-GC-MS) and headspace gas chromatography-ion mobility spectrometry (HS-GC-IMS), the differences in volatile flavor compound composition and overall flavor profile of the three types of lamb meat were systematically analyzed and compared. Qualitative analysis of flavor compounds was conducted using GC-MS and principal component analysis (PCA) was used to identify the dominant factors affecting flavor differences in different types of lamb meat; Using GC-IMS to obtain fingerprint and two-dimensional differential spectra of volatile substances, achieving intuitive and sensitive differentiation of three types of lamb flavor characteristics. The results showed that GC-MS identified a total of 19 volatile substances, including 8 aldehydes, 5 alcohols, 4 esters, and 2 other compounds. Among them, 16 were detected in Tibetan sheep, 11 in local sheep and 15 in goats. The content of aldehydes such as hexanal and heptanal in Tibetan sheep was significantly higher than that in the other two types of lamb meat; GC-IMS detected a total of 26 volatile compounds, including 8 esters, 6 aldehydes, 9 alcohols and 2 others. Butyl formate and n-hexanol are characteristic flavor compounds of Tibetan sheep, while 2-furanyl methanol acetate is a unique substance of goats. Principal component analysis shows that aldehydes are the core contributing category to the flavor differences among the three types of lamb meat; The HS-GC-IMS fingerprint spectrum intuitively presents the differences in the content and types of three volatile substances in lamb meat.trans-2-Decenal, 1-octen-3-ol, hexanal, 2-heptenal, and nonanal were identified as key volatile compounds through the combination of variable importance in projection (VIP) from PLS-DA and ROAV. The aroma profile radar chart shows that Tibetan sheep exhibit a prominent fatty aroma, goat displays a distinct mushroom-like aroma, while sheep overall present a mild odor. Two analytical techniques collaborated to verify significant differences in volatile flavor compounds among Tibetan sheep, local sheep and goats, providing theoretical basis and data support for lamb breed identification, quality evaluation and development of specialty meat products.